PENGEMBANGAN BUKU AJAR KONTEKS SITUASI DAN SOSIAL DALAM PRAGMATIK EDUKASIONAL - Sembiring, Rehulina Juniarti BR.; Pranowo, Pranowo; Rahardi, R. Kunjana (Universitas Pendidikan Indonesia, 2018)
This research aims to develop textbook situation and social context in pragmatic educational methods of research and development (R D) the Borg and Gall are modified into 8 development procedures. The results showed: (1) there is a context of abai's behavior carried out by students, (2) lack of understanding of students regarding the integration of the social situation and context as well as its application in the educational, and pragmatics (3) necessity developed educational textbook about pragmatics with integrating social situations and contexts in it. As well, the results of the development shows that textbook that has been developed is worthy to be used with the results of validation experts from the aspect of the look, the linguistic material, and get an average score of 3.79 by category. The results of the assessment of the students from the aspect of the look, the linguistic material, and get an average score of 3.65 with very good category, as well as assessment of the lecturers pengampu courses from the aspect of the look, the linguistic material, and get an average score of 4.00 with the category very well.